Psychometric properties of the Dysexecutive Questionnaire (DEX): a study with Brazilian older adults - Oliveira, Camila Rosa de (2021)
This study aimed to verify the psychometric properties of the Dysexecutive Questionnaire (DEX) through exploratory factor analysis (EFA), evidence of reliability, and convergent validity, in a sample of neurologically preserved older adults. Participants were 345 older adults who answered, in addition to DEX, a sociodemographic and clinical questionnaire, the Mini-Mental State Examination (MMSE), and two verbal fluency tasks. The EFA was conducted through Parallel Analysis based on the generation of a polychoric correlation matrix, as well as Pearson’s correlation between the DEX scores, age, education, MMSE, and verbal fluency tasks. According to the EFA, the extraction of two factors (“Inhibition” and “Social Regulation and Planning”) was suggested and DEX was negatively associated with age and MMSE. In conclusion, DEX presented a satisfactory factorial structure for older adults, which can be considered a reliable self-report measure for complaints of executive functions. Keywords: